(3fgGjI GdEMcGe aj eYQaI GdCMcGes - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3hZjQgG(B... (3haj GdHdGA (B... (3hZjQgG dYOe Jhba GdcQGgjI Ydi Nha GdeMPhQs
(3BNQgG (B:s
(3dh cGf GdHYV aj GdLfS hGdHYV ef ZjQg HWd aj ZjQ GdLfS hJNjQ GdeTJQj dJaQb(B... (3gPG BNQ eG hLO ef gPG GdcJGH hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B689s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis